2023
DOI: 10.1007/s13132-023-01260-6
|View full text |Cite
|
Sign up to set email alerts
|

Financial Development and Unemployment in MENA: Evidence from Heterogeneous Panel Causality and Quantile via Moment Regression

Abstract: The high rate of unemployment is one of the socio-economic problems bedevilling the MENA region. Theoretical and empirical arguments remain divided regarding financial development’s role in addressing unemployment. In light of this, this study investigates the effect of financial development on different components of unemployment (total (adult and youth) and gender (male and female)) in MENA. To capture financial development, we used the IMF composite financial development index. For robustness, we also compu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 71 publications
0
3
0
Order By: Relevance
“…Some authors [ 28 , 31 ] demonstrated a negative association for EU countries. Same negative association was proved for OECD countries [ 29 ] or for Middle East and North-African countries [ 32 ].…”
Section: Discussion Of Resultsmentioning
confidence: 75%
See 2 more Smart Citations
“…Some authors [ 28 , 31 ] demonstrated a negative association for EU countries. Same negative association was proved for OECD countries [ 29 ] or for Middle East and North-African countries [ 32 ].…”
Section: Discussion Of Resultsmentioning
confidence: 75%
“…The ability to provide real and accurate findings in the presence of outlier data [ 40 ], the flexibility of coefficients throughout the distribution [ 41 ], freedom from problems related to sample selection bias [ 42 ], and the ability to explain the effect of independent variables (regressors) on the dependent variable in different quantiles [ 43 ] are among its most significant advantages. Several economic studies have used the quantile regression method to investigate the relationships between variables [ 32 , 44 , 45 ]. Estimating in different quantiles is important in economics because the relationship between variables is often non-linear.…”
Section: Model and Methodologymentioning
confidence: 99%
See 1 more Smart Citation